A JOURNEY FROM BEING THE RICHEST TO THE POOREST CONTINENTAL – A STUDY ON AFRICA’S HEALTH, EDUCATION AND AGRICULTURE SECTOR - Dr.Sumanta Bhattacharya; Dr. Jayanta Kumar Ray; Shakti Sinha; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
From being home to the richest people in the world , Africa today has become an impoverishment continent which has given birth to uncountable problems which has acted as a hurdle in the development and sustainable growth of the continent , it is the second largest continent in the world which has high poverty rate , hunger problem , the continent is home to maximum number of diseases , with lack of basic health care facilities , with 600 million people having no access to electricity , food shortage , agricultural problems , lack of infrastructure, food shortage and lack of education . Education and health care are two important ingredients that are required for the economic and social development of a continent.Africa needs to adopt new measures and policies in the sector of education , health , food security , water policy for the development and trying to bring positive changes as the political system of Africa is itself responsibility for the lack of development in Africa followed by the religion and mentality .With the COVID situation the situation has turned out to be worst with lack of education and health care facility , no access to safe drinking water , more and more people are dying . Basic material and necessity needs to be provided to all its people for survival of Africa